Cardiomyopathy of Friedreich's Disease. Modern Methods of Diagnostic - E. I. Fomicheva; R. P. Myasnikov; Y. A. Selivyorstov; S. N. Illarioshkin; E. L. Dadali; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Friedreich's disease is a hereditary neurodegenerative multiple organ disease, primarily affecting the most energy-dependent tissues (cells of the nervous system, myocardium, pancreas), the lesion of which is characterized by progressive ataxia, dysarthria, dysphagia, oculomotor disorders, loss of deep tendon reflexes, pyramid signs, diabetes mellitus, visual impairment. Friedreich's ataxia is the most common of all hereditary ataxias; nevertheless, this disease is considered orphan. By its pathogenesis, Friedreich's disease is mitochondrial ataxia, caused by a deficiency in the transcription of the FXN gene, leading to a decrease in the synthesis of the frataxin protein. Frataxin is a protein associated with the inner mitochondrial membrane, which in turn is involved in the formation of iron-sulfur clusters, the lack of which leads to a decrease in the production of mitochondrial ATP, an increase in the level of mitochondrial iron and oxidative stress. The basis of the clinical picture of Friedreich's disease is ataxia of a mixed (sensitive and cerebellar) nature. The steady and gradual progression of neurological symptoms significantly affects the quality of life of patients and is most often the leading reason for seeking medical attention. However, the prognosis is primarily due to the involvement of cardiac tissue in the pathological process. The main causes of death in patients with Friedreich's ataxia are severe heart failure and sudden cardiac death due to cardiomyopathy. The overwhelming majority of foreign and domestic publications on Friedreich's ataxia are devoted to the neurological manifestations of this disease, and little attention is paid to this problem in the cardiological scientific and practical society. The purpose of this review is to provide up-to-date information on modern methods of diagnosing myocardial damage at various stages of Friedreich's disease.